The Asylum Procedure in Germany: Desperation and Uncertainty as Risk Factors for Violence Among Young Adult Asylum Seekers in Collective Accommodations - Al Ajlan, Ahmad (Journal of interpersonal violence, 2022)
This study explores how violence occurs among young adult asylum seekers in collective accommodations in the state of North Rhine-Westphalia in Germany. It provides an insider perspective to understand a phenomenon related to non-European people who were forced to leave their countries to seek asylum. Based on 16 qualitative interviews with young adult male asylum seekers from Syria and some African countries, seven interviews with social workers, and one interview with a German psychological therapist, the author finds that the asylum procedure in Germany as a total institution catalyzes violence among young adult asylum seekers in collective accommodations. The present study shows that collective accommodations are unhomely places, where ?inmates? lack privacy and autonomy. In addition, the asylum procedure deprives them of essential human needs, such as the right to work and to have full access to the health care system. These circumstances make them uncertain and desperate, which leads to violence among them. The author calls for more attention towards the human needs of asylum seekers, rather than making them related to the granting of asylum, which can ultimately take years.